Unoccupied electronic states in atomic chains on Si(557)-Au: Time-resolved two-photon photoemission investigation - Rügheimer, Tilman; Fauster, Thomas; Himpsel, F. J. (Physical Review B, 2007)
The prototypical one-dimensional Si(557)-Au surface is investigated with time-resolved two-photon photoemission. Three new states are found near (Gamma) over bar, two of them in the band gap of silicon. These states cannot be explained by existing band calculations. As a possible solution, we suggest a closer examination of the atomic and electronic structure near the step edge.